2004
DOI: 10.3102/00028312041003605
|View full text |Cite
|
Sign up to set email alerts
|

Accountability in a Postdesegregation Era: The Continuing Significance of Racial Segregation in Florida’s Schools

Abstract: In the wake of both the end of court-ordered school desegregation and the growing popularity of accountability as a mechanism to maximize student achievement, the authors explore the association between racial segregation and the percentage of students passing high-stakes tests in Florida’s schools. Results suggest that segregation matters in predicting school-level performance on the Florida Comprehensive Assessment Test after control for other known and purported predictors of standardized test performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…The positive influence of race/ethnic diversity for educational success is observed as early as elementary school, and this work early in the life course highlights diversity benefits for both children's academic performance and their socioemotional well-being (Benner & Crosnoe, 2011; Borman & Eitle, 2004). In contrast, mathematics and reading achievement, mental health, and interpersonal functioning is poorer when children attend segregated schools with a high percentage of race/ethnic minority youth (typically operationalized as the percentage of African American and Latino students in the school; Benson & Borman, 2010; Crosnoe, 2005).…”
Section: Race/ethnic Diversity and Children's Developmentmentioning
confidence: 86%
“…The positive influence of race/ethnic diversity for educational success is observed as early as elementary school, and this work early in the life course highlights diversity benefits for both children's academic performance and their socioemotional well-being (Benner & Crosnoe, 2011; Borman & Eitle, 2004). In contrast, mathematics and reading achievement, mental health, and interpersonal functioning is poorer when children attend segregated schools with a high percentage of race/ethnic minority youth (typically operationalized as the percentage of African American and Latino students in the school; Benson & Borman, 2010; Crosnoe, 2005).…”
Section: Race/ethnic Diversity and Children's Developmentmentioning
confidence: 86%
“…A plethora of literature indicates that the racial and socioeconomic (SES) composition of a school's student body is related to the academic climate and resources that optimize opportunities to learn. Schools with concentrations of disadvantaged minority and poor youth are less likely to have highly qualified teachers, peers who demonstrate that they value academic excellence, or the opportunity to enroll in advanced levels of core academic classes that prepare students for college success (Bankston &Caldas, 1996;Borman et al, 2004;Hanushek, Kain, & Rivkin, 2009;Jackson, 2009;Lleras, 2008;Mickelson et al, 2013a;Mickelson & Nkomo, 2012;Palardy, 2013;Rumberger & Palardy, 2005;Kelly, 2009;Teranishi & Parker, 2010).…”
Section: Racial/ethnic and Socioeconomic Composition Of The Schoolmentioning
confidence: 93%
“…63 One study using National Assessment of Educational Progress (NAEP) data across every state found that when controlling for socioeconomic status, most of the negative relationship with segregated schools and achievement is eliminated for whites but not for black students, although the relationship varied among states. 64 A recent study in Texas analyzed the impact of racial composition of classmates on the test scores of students, from 4th to 7th grade.…”
Section: The Benefits Of Racially Integrated Schools For Studentsmentioning
confidence: 99%